A study on factors that influence international students choice to further studies at Universiti Tun Hussein Onn Malaysia (UTHM) / Muhamad Shahrulfitri Mohd Sulaiman - Mohd Sulaiman, Muhamad Shahrulfitri (Faculty of Business and Management, 2014)
Every university and institution must have the ability in order to attract students, either local or foreign, it has become a crucial advantage in the competitive between higher education institution even private and public university. However, research looking into international students’ perceptions on university selection is still very lacking in the local setting. Thus, this study aims to identify the factors that influence the national students choice to further studies at Universiti Tun Hussein Onn Malaysia (UTHM) and to verify their relationships. The results indicated that university/institution reputation, education facilities, and cost and fee (financial factor) were having significant relationships with international students’ choice to further studies at Universiti Tun Hussein Onn Malaysia (UTHM). Recommendations for future research have also been put out in this paper.